Productivity Decomposed: Getting Big Things Done with Little Microtasks - Teevan, Jaime; Bigham, Jeffrey P.; Iqbal, Shamsi; Bernstein, Michael S.; Cai, Carrie J.; Gerber, Elizabeth M. (A workshop at the ACM Conference on Human Factors in Computing Systems (CHI 2016), San Jose, CA, 2016)
It is difficult to accomplish meaningful goals with limited time and attentional resources. However, recent research has shown that concrete plans with actionable steps allow people to complete tasks better and faster. With advances in techniques that can decompose larger tasks into smaller units, we envision that a transformation from larger tasks to smaller microtasks will impact when and how people perform complex information work, enabling efficient and easy completion of tasks that currently seem challenging. In this workshop, we bring together researchers in task decomposition, completion, and sourcing. We will pursue a broad understanding of the challenges in creating, allocating, and scheduling microtasks, as well as how accomplishing these microtasks can contribute towards productivity. The goal is to discuss how intersections of research across these areas can pave the path for future research in this space.